The Manifestation of Teacher Leadership in Vietnamese National Educational Policy Documents (Journal of Contemporary Educational Policies and Practices, 2022)
The critical importance of teacher leadership roles in students’ academic achievements and school improvement is widely recognized. Preparing teachers for taking leadership roles, therefore, is requisite, particularly in response to the dynamic and changing nature of the present-day teaching profession. However, there is a lack of research into how teachers are provided with skills and knowledge to serve the leadership role, both formally and informally. The study employed The Teacher Leader Model Standards (TLMS) developed by the Teacher Leadership Exploratory Consortium (2011) to explore the manifestation of teacher leadership knowledge and competencies in policies on the teaching profession in the Vietnamese context. The analysis of 61 in-effect national policy documents on teaching profession standards and teacher professional development programs reveals that these policy documents have presented a broad but incomplete view of teacher leadership. Percentage-wise, teacher leadership is far from a salient manifestation within policy documents, indicating that it has not yet been considered a core competence in the teaching profession at the national policy level. In addition, there are crucial aspects of teacher leadership that have been neglected, while a lack of differentiation between teacher and principal leadership still remains in the documents. Based on the findings, the study proposes recommendations to the teachers, school leaders and policy makers on the development of teacher leadership.
Keywords: Policy analysis; teacher leadership competence; the South of Vietnam